Rites–Christian and Non-Christian–In A Cosmic Liturgy of Fraternity - Abeyasingha, Nihal (Archīum Ateneo, 2022)
The present article starts from the Past-Present-Future dimensions of sacraments, to which Vagaggini has added the moral-dispositive element (commitment). These four dimensions within the Christian perspective can be analysed as (1) anamnesis, presentation of gifts and persons, (2) epiclesis, invoking Spirit to transform gifts and weld together persons, (3) eschatology, and (4) theosis. When applied in a non-Christian environment, one can expand these four elements in terms of (1) narration (memory), (2) presentation of themselves through whatever gestures, (3) fulfillment/maturation and, (4) generativity. Through this analysis, one can speak of even non-Christians being united in a cosmic liturgy in the spirit of Teilhard de Chardin.